Distinct Role of a Spring Atmospheric Circulation Mode in the Arctic Sea Ice Decline in Summer. Issue 6 (17th March 2023) - Bi, Haibo; Liang, Yu; Chen, Xianyao
Abstract: A distinguishing feature of Arctic sea ice is the rapid declining in the Pacific Arctic Sector (PAS) in recent years. The atmospheric variability during spring (March‐May) plays a critical role in determining the sea ice extent (SIE) during the following summer. The summertime (June‐August) SIE reduction in the eastern part of PAS, including the East Siberian Sea and the Laptev Sea, is strongly related to the first two leading atmospheric circulation modes in spring, the Arctic Oscillation and the Arctic Dipole, retrieved from empirical orthogonal function analysis. Here, we show that the third leading mode of atmospheric circulation in spring, namely the Barents‐Beaufort Oscillation (BBO), can also change the summer SIE, especially on the western regime of the PAS across the Beaufort and Chukchi Seas. We find that a positive phase of springtime BBO (i.e., BBO+), relative to the BBO−, acts to decrease sea ice thickness via advection and generate sea ice deformation through divergence and shear processes, thereby preconditioning for a rapid sea ice loss within the PAS in the following summer. Furthermore, the occurrence of BBO is state‐dependent and potentially modulated by the phase shift of the Atlantic Multidecadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO). Since the mid‐1990s, the AMO (PDO) index has changed from a dominant negative (positive) to a positive (negative) phase. These phase shifts in AMO and PDO would have contributed to the subsequently increased appearance of anomalous BBO+ after 2000 and enhanced the summertime sea ice loss in the western regions of the PAS in recent years. Plain Language Summary: Large‐scale atmospheric circulation plays a vital role in regulating the Arctic sea ice extent (SIE) changes in summer. Spring atmospheric circulation anomaly could precondition for a noticeable decline in SIE in the following summer. Arctic Oscillation and Arctic Dipole anomaly modes are well demonstrated in previous studies. In this study, we outline the effectiveness in leading to sea ice reduction by another important circulation pattern, namely the Barents‐Beaufort Oscillation (BBO). The spring BBO in its positive phase can change the summer SIE over the western Pacific‐Arctic sector, including Beaufort and Chukchi Seas. The two seas are the regions undergoing the rapidest shrinkage over the past decades. We also found that the decadal variability of BBO seems to be associated with the ocean activities at low latitudes. The frequent occurrence after 2000 is partly attributable to the phase shift by the Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation since mid‐1990s. Key Points: A special connection of summer Arctic sea ice extent shrinkage to spring Barents‐Beaufort Oscillation (BBO) is outlined The dynamic impacts on ice thickness decline through diverging and shearing processes linked to BBO are identified over the Pacific‐Arctic sector The effectiveness of BBO on Arctic sea ice changes depends on the states of Atlantic Multidecadal Oscillation and Pacific Decadal Oscillation